A Comparison of Epithelial Cells, Fibroblasts, and Osteoblasts in Dental Implant Titanium Topographies. (12th January 2012) - Teng, Fu-Yuan; Ko, Chia-Ling; Kuo, Hsien-Nan; Hu, Jin-Jia; Lin, Jia-Horng; Lou, Ching-Wen; Hung, Chun-Cheng; Wang, Yin-Lai; Cheng, Cheng-Yi; Chen, Wen-Cheng
Abstract : The major challenge for dental implants is achieving optimal esthetic appearance and a concept to fulfill this criterion is evaluated. The key to an esthetically pleasing appearance lies in the properly manage the soft tissue profile around dental implants. A novel implant restoration technique on the surface was proposed as a way to augment both soft- and hard-tissue profiles at potential implant sites. Different levels of roughness can be attained by sandblasting and acid etching, and a tetracalcium phosphate was used to supply the ions. In particular, the early stage attaching and repopulating abilities of bone cell osteoblasts (MC3T3-E1), fibroblasts (NIH 3T3), and epithelial cells (XB-2) were evaluated. The results showed that XB-2 cell adhesive qualities of a smooth surface were better than those of the roughened surfaces, the proliferative properties were reversed. The effects of roughness on the characteristics of 3T3 cells were opposite to the result for XB-2 cells. E1 proliferative ability did not differ with any statistical significance. These results suggest that a rougher surface which provided calcium and phosphate ions have the ability to enhance the proliferation of osteoblast and the inhibition of fibroblast growth that enhance implant success ratios.